2014
DOI: 10.12968/bjon.2014.23.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in exclusive breastfeeding: a systematic review

Abstract: Aim of the paper:To examine current literature surrounding variables which may affect the initiation and maintenance of breastfeeding.Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…43 In this study, there was no significant relationship between family members and the practice of exclusive and non-exclusive breastfeeding (P = 0.770). These findings were not in line with studies conducted by Brand et al, 46 Bevan and Brown, 47 and Demirtas, 48 as they reported that the presence of partners and families play a significant role in helping and supporting mothers to continue exclusive breastfeeding for six months, thereby significantly decreasing the risk of early discontinuation of exclusive breastfeeding.…”
Section: Competing Interestscontrasting
confidence: 56%
“…43 In this study, there was no significant relationship between family members and the practice of exclusive and non-exclusive breastfeeding (P = 0.770). These findings were not in line with studies conducted by Brand et al, 46 Bevan and Brown, 47 and Demirtas, 48 as they reported that the presence of partners and families play a significant role in helping and supporting mothers to continue exclusive breastfeeding for six months, thereby significantly decreasing the risk of early discontinuation of exclusive breastfeeding.…”
Section: Competing Interestscontrasting
confidence: 56%
“…It seems that a multi-pronged approach may be most appropriate with some interventions being focused on specific groups such as in urban areas or at private hospitals. This phenomenon has been explored and may explain why some interventions are less effective in different settings [ 19 21 ]. Related to the findings about mother’s BF knowledge, mothers who lived in urban areas and were further educated, also uniquely reported using social media to access breastfeeding knowledge, and provide or receive group or peer support to encourage continuation of EBF.…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of interventions and programs has been implemented in various contexts to promote breastfeeding initiation, duration, and exclusivity, with varying degrees of success. Interventions have included strategies such as peer counselling, professional counselling, online support, phone support, antenatal breastfeeding education, multimedia approaches, motivational interviewing, breastfeeding-friendly hospital practices, breastfeeding-friendly workplaces, and parental leave policies [21][22][23][24][25][26][27][28]. Despite this extant research, young mothers do not appear to be well represented in these intervention studies.…”
Section: Introductionmentioning
confidence: 99%